2007
DOI: 10.1016/j.molcata.2007.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of liquid property on adsorption and catalytic reduction of nitrate over hydrotalcite-supported Pd-Cu catalyst

Abstract: This study focused on investigating the effect of liquid property on adsorption and catalytic reduction of nitrate over hydrotalcite-supported Pd-Cu catalyst. Batch experiments were conducted under specific operating conditions. It was found that nitrate ions were adsorbed apparently by hydrotalcite-supported Pd-Cu catalyst at different reaction temperature (10, 25 and 35• C). Adsorption isotherms for NO 3 − were described by Langmuir's equation. Higher reaction temperature accelerated nitrate adsorption and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 21 publications
2
9
0
5
Order By: Relevance
“…Accordingly, the current technologies used for nitrate removal from water receive an increasing attention. Based on the property of HT, a novel hydrotalcite-supported Pd-Cu material, combining the high adsorption capacity of HT and the reduction property of active metals (Pd-Cu) for nitrate, were developed (Wang Y, 2006;Wang et al, 2007a). In this case, HT was used not only as an adsorbent but also as a catalyst support.…”
Section: Hydrotalcite-supported Pd-cu Adsorbent For Nitrite Removalmentioning
confidence: 99%
“…Accordingly, the current technologies used for nitrate removal from water receive an increasing attention. Based on the property of HT, a novel hydrotalcite-supported Pd-Cu material, combining the high adsorption capacity of HT and the reduction property of active metals (Pd-Cu) for nitrate, were developed (Wang Y, 2006;Wang et al, 2007a). In this case, HT was used not only as an adsorbent but also as a catalyst support.…”
Section: Hydrotalcite-supported Pd-cu Adsorbent For Nitrite Removalmentioning
confidence: 99%
“…Since the catalysts had excellent adsorptive ability toward anions, the nitrites concentration was to a much lower extent. In the previous study of our group, it was demonstrated that hydrotalcite-supported Pd/Cu catalysts had both excellent adsorption and catalytic properties for nitrate reduction [31,32]. Also, the catalyst synthesized via a coprecipitation method exhibited higher adsorption and catalytic activity than that prepared by coimpregnation method [31].…”
Section: Introductionmentioning
confidence: 95%
“…on the metallic active sites [23][24][25], which led to a decrease in catalytic activity and selectivity. Wang et al [22] reported that, although a Cu-Pd/activated carbon catalyst showed high activity, selectivity for the formation of N 2 and N 2 O, and durability for the reduction of 100 mg/L NO − 3 in distilled water, the catalytic performance decreased in the case of the reduction of NO − catalyst deactivation.…”
Section: Introductionmentioning
confidence: 99%